Effect of Titanium Particles on the Voltage-Gated Potassium Channel Currents in Trigeminal Root Ganglion Neurons. Issue 1 (February 2019) - Song, Ning; Liao, Da-Qing; Liu, Fei; Zhang, Yan-Yan; Lin, Jiu; Wang, Hang; Shen, Jie-Fei
Abstract : Purpose: Titanium (Ti) is the key material used in dental implants because of its excellent biocompatibility. But wear and corrosion Ti particles had been widely reported to induce inflammation and promote bone absorption. However, little information is known about the damage of Ti particles on neurons. Materials and Methods: Trigeminal root ganglion (TRG) neurons were exposed to Ti particles (<5 μm). The electrophysiological properties of 2 main subtypes of voltage-gated potassium channels (VGPCs) (KA and KV ) were examined by whole-cell patch-clamp techniques. Result: With the presence of 0.25 mg/mL Ti particles, amplitudes of IK, A and IK, V were both obviously inhibited. For IK, A, the activation V1/2 shifted to the depolarizing direction with an increased k value, whereas the inactivation V1/2 showed obvious hyperdepolarizing shifts. For IK, V, 0.5 mg/mL Ti particles produced a depolarizing shift of activation V1/2 with a slower activation rate. No significant changes of its inactivation kinetics were found. Conclusion: Titanium (Ti) particles might alter the electrophysiological properties of VGPCs on TRG neurons, which are likely to further influence the excitability of neurons.